SAT0206 Retention of tocilizumab as monotherapy versus tnf inhibitors with conventional synthetic dmards in rheumatoid arthritis patients with inadequate response to tnf inhibitors: a study from the tocerra collaboration. (15th June 2017) - Lauper, K; Nordström, DC; Pavelka, K; Hernandez, V; Santos, MJ; Rotar, Z; Iannone, F; Codreanu, C; Lukina, G; Gale, SL; Sarsour, K; Pethoe-Schramm, A; et al.
Abstract : Background: Tocilizumab (TCZ) as monotherapy has been shown to be more efficacious than the TNF inhibitor (TNFi) adalimumab as monotherapy in patients with rheumatoid arthritis (RA). However, effectiveness data comparing TCZ as monotherapy versus TNF inhibitors in combination with csDMARDs are limited. Objectives: To examine retention of TCZ administered alone (TCZ mono) versus TNFi in combination with csDMARDs (TNFi combo) in patients with RA who had an inadequate response to ≥1 TNFi (TNFi-IR). Methods: Patients with RA who were TNFi-IR and treated with TCZ mono or TNFi combo with baseline (BL) data, not immediately lost to follow-up and started treatment after TCZ was available across 9 European registries in TOCERRA from 2009 to 2016 were included. The hazard for TCZ discontinuation was modeled using a country-stratified Cox proportional hazards model, adjusting for age, gender, disease duration, seropositivity, HAQ and CDAI at BL, number of previous csDMARD and biologic DMARD (bDMARD), glucocorticosteroid and calendar year of treatment initiation. Missing data on covariates were imputed using multiple imputation with chained equations. Results: A total of 4748 patients were eligible, including 585 who received TCZ mono and 4163 who received TNFi combo. Patients who received TCZ mono were older with a longer disease duration, more previous bDMARDs and less glucocorticosteroids at baseline (Table 1 ) compared with patients who received TNFi combo. The crude median retention for TCZ mono was 1.82 years (95% CI: 1.59–2.09) and 1.54 years (95% CI: 1.43–1.64) for TNFi combo, ( P =0.65). Causes of discontinuation differed between TCZ mono and TNFi combo ( P <0. 001): TCZ mono stopped more frequently for ineffectiveness (25.7% vs. 13.8%) and TNFi combo stopped more frequently for safety issues (18.3% vs. 12.8%). In a country-stratified, covariate-adjusted analysis, we found that hazards of discontinuation were significantly lower among patients who received TCZ mono (HR: 0.71, P <0.001). More previous treatment with bDMARDs and a greater HAQ and CDAI at BL were significantly associated with greater risk of discontinuation. Conclusions: In routine care across 9 European countries, TCZ mono retention is better than TNFi combo in patients with RA who were TNFi-IR. Acknowledgements: Funding by F. Hoffmann-La Roche/Genentech. Disclosure of Interest: K. Lauper: None declared, D. Nordström Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB, Consultant for: AbbVie, BMS, MSD, Roche, UCB and Pfizer, K. Pavelka Grant/research support from: AbbVie, Roche, Medis, MSD and Pfizer, Consultant for: AbbVie, Roche, Amgen, MSD, BMS, UCB and Egis, V. Hernandez: None declared, M. J. Santos: None declared, Z. Rotar: None declared, F. Iannone: None declared, C. Codreanu: None declared, G. Lukina Consultant for: BMS, Roche, MSD, AbbVie and Pfizer, S. Gale Employee of: Genentech, K. Sarsour Employee of: Genentech, A. Pethoe-Schramm Employee of: F. Hoffmann-La Roche, D. Courvoisier: None declared, C. Gabay Grant/research support from: AB2 Bio, AbbVie, Actelion, BMS, Debiopharm, MSD, Novartis, Pfizer, Regeneron, Roche, Sanofi and UCB, Consultant for: AB2 Bio, AbbVie, Actelion, BMS, Debiopharm, MSD, Novartis, Pfizer, Regeneron, Roche, Sanofi and UCB